Intermediary Devices in the Contemporary Scene (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2026)
This article addresses the concept of Spatial Augmented Reality applied to contemporary performing arts, linking it to other concepts intrinsic to staging and acting, such as presence, organicity, and the precision of physical action scores. These concepts are examined through the lens of the following contemporary plays: “Enquanto você voava eu criava raízes” (2022) by Cia. Dos a Deux from Brazil, “The Wooster Group’s Hamlet” (2013) by The Wooster Group from United States of America and “La belle et la bete” (2011) by Cia. 4dArt from Canada.  These plays were chosen because their scenic constructions integrate intermedial devices that add virtual images in direct relation to the actors on stage
Keywords: intermediality; virtual theater; Performance